2013
DOI: 10.1371/journal.pone.0063684
|View full text |Cite
|
Sign up to set email alerts
|

The Human Fetus Preferentially Secretes Corticosterone, Rather than Cortisol, in Response to Intra-Partum Stressors

Abstract: ContextFetal stress is relevant to newborn outcomes. Corticosterone is rarely quantified in human clinical endocrinology and is found at much lower concentrations than cortisol. However, fetal corticosterone is a candidate hormone as a fetal stress signal.ObjectiveTest the hypothesis that preferential fetal corticosterone synthesis occurs in response to fetal intra-partum stress.DesignCross-sectional comparison of paired serum corticosteroid concentrations in umbilical artery and vein from 300 women providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…In general, maternal stress raises corticosterone concentrations during pregnancy with negative effects on a feto‐placental unit (Jafari, Mehla, Afrashteh, Kolb, & Mohajerani, ; Vaughan, Sferruzzi‐Perri, & Fowden, ). Elevations in corticosterone rather than cortisol concentrations strongly correlate with fetal stress in human studies (Wynne‐Edwards, Edwards, & Hancock, ). Despite elevated corticosterone in maternal circulation, corticosterone and DOC, which are both downstream products in the adrenal steroidal pathway leading to aldosterone synthesis, were lower in the D90 BPA‐exposed female fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…In general, maternal stress raises corticosterone concentrations during pregnancy with negative effects on a feto‐placental unit (Jafari, Mehla, Afrashteh, Kolb, & Mohajerani, ; Vaughan, Sferruzzi‐Perri, & Fowden, ). Elevations in corticosterone rather than cortisol concentrations strongly correlate with fetal stress in human studies (Wynne‐Edwards, Edwards, & Hancock, ). Despite elevated corticosterone in maternal circulation, corticosterone and DOC, which are both downstream products in the adrenal steroidal pathway leading to aldosterone synthesis, were lower in the D90 BPA‐exposed female fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…where labour had occurred), compared with delivery by elective Caesarean section (i.e. pre-labour) 10 , 12 , 14 . Our finding of higher corticosterone (but not cortisol) in labouring cord samples was in-keeping with a previous study 14 who found highest corticosterone levels in vaginal deliveries, followed by emergency caesarean deliveries (who would have laboured), and lowest levels in elective caesarean deliveries (no labour).…”
Section: Discussionmentioning
confidence: 99%
“…As offspring born to obese women are more likely to need respiratory support at delivery 9 , it is plausible that exposure to comparatively lower levels of glucocorticoids in utero could limit fetal lung maturation in this group. One previous study reported lower maternal cortisol, but not cord cortisol at delivery in obese compared to normal weight women 4 , but did not adjust for mode of delivery or labour; both factors are known to influence cord cortisol levels 10 14 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cortisol quantitation by Agilent 1200 Liquid Chromatography (LC) coupled to ABSciex 5500 qTrap Tandem Mass Spectrometry (MS/MS) (atmospheric pressure chemical ionization ¼ APCI source) used the area ratio against an internal deuterated cortisol standard (cortisol d4, D-5280, CDN isotopes, Pointe-Claire, Quebec, Canada). 7 The lower limit of quantitation (LLOQ) with a minimum of 50 µL of sample was 0.075 µg/dL. We measured free cortisol levels in saliva and total cortisol levels in serum.…”
Section: Methodsmentioning
confidence: 99%